2013
DOI: 10.1002/lt.23565
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose steroids associated with milder histological changes after pediatric liver transplantation

Abstract: Controversy remains about the role of protocol liver biopsy for symptom-free recipients and about the long-term use of lowdose steroids after pediatric liver transplantation (LT). We conducted a national cross-sectional study of pediatric recipients who underwent LT between 1987 and 2007. Liver biopsy samples were taken from 54 patients (82% of survivors) after a median posttransplant follow-up of 11 years, and they were reviewed by 2 pathologists blinded to the clinical data. Biopsy samples from 18 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 36 publications
6
61
1
Order By: Relevance
“…In adult patients with NAFLD, the NAFLD fibrosis score, the AST/platelet ratio index, and the BARD score predicted liver‐related events, and the NAFLD fibrosis score also predicted death or LT . Among our patients, however, the AST/platelet ratio index was low (median = 0.42) and showed no connection to liver steatosis, and liver fibrosis was mainly METAVIR stage 1; this makes the proposed predictive systems inapplicable.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In adult patients with NAFLD, the NAFLD fibrosis score, the AST/platelet ratio index, and the BARD score predicted liver‐related events, and the NAFLD fibrosis score also predicted death or LT . Among our patients, however, the AST/platelet ratio index was low (median = 0.42) and showed no connection to liver steatosis, and liver fibrosis was mainly METAVIR stage 1; this makes the proposed predictive systems inapplicable.…”
Section: Discussionmentioning
confidence: 65%
“…Five patients also had macrovesicular steatosis in up to 33% of hepatocytes. The greatest NAFLD activity score was 1 for all patients, and no cases of steatohepatitis were encountered …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Only a few cases of late HAT were present in a pediatric protocol liver biopsy study; therefore, putting our findings (although not significant) in context with other protocol liver biopsy studies remains open. A recent study from our center observed a correlation between GGT and chronic cholestasis, and this study (examining a subset of patients from ref. 11) also showed a correlation between GGT and chronic cholestasis.…”
Section: Discussionmentioning
confidence: 97%
“…Liver biopsy was performed as part of the routine clinical follow‐up protocol regardless of patient symptoms. A detailed description of the histological methods and the results of biopsy findings have been reported previously . Briefly, core needle biopsy was performed under ultrasound guidance, and biopsy specimens were fixed, embedded, and stained with conventional histochemical methods.…”
Section: Methodsmentioning
confidence: 99%